Kemampuan Biofilter Anaerob Berdasarkan Jenis Media dalam Pengolahan Air Limbah Domestik Tahun 2016 - Donal Nababan; Mido Ester Juniati Sitorus; Ivan Elisabeth Purba; Netti Etalia Br. Brahmana; Evawani Martalena Silitonga (Jurnal Riset Hesti Medan, 2019)
Domestic wastewater is used water that cannot be used anymore for its original use, either containing human waste (feces) or from kitchen, bathroom and washing activities. The more dense the population in a settlement the more waste must be controlled. One simple way to treat domestic wastewater is to use anaerobic biofilter based on the type of media. The media used were broken stones, plastic sheets, and coconut shell charcoal. The purpose of this study was to determine the ability of anaerobic biofilter based on the type of media in domestic wastewater treatment. The parameters measured are BOD, COD and PH. Anaerobic biofilter performance is determined by looking at the difference in levels before and after using the media. This research is a quasi-experimental research with one group pretest-posttest design. The sample of this study were 10 samples taken from repetition 3 times in one experiment, the process was done by a batch system. The results showed an average reduction in BOD on plastic sheet media by 84.76%, COD by 84.77%, PH by 32.3%. The average reduction in BOD in the stone medium was 80.57%, COD was 80.59%, PH was 29.66%. The average reduction in BOD in coconut shell charcoal media was 69.72%, COD was 77.84%, PH was24%.